Health, Power, and Multiple Subjectivities: The Governance of Maternal and Child Body under the Medicalizing State - Op-ai, Pattarawadee (Journal of Social Sciences Naresuan University, 2026)
This study examined the operation of a medicalized state through the project “Miracle First 1,000 Days of Life” in Borkaew Subdistrict, Samoeng District, Chiang Mai Province. It aims to investigate the practices of technologies of power in regulating and managing the body, as well as how parents participating in the program navigate and respond to these regulations. A qualitative research approach was employed, with data collected through document analysis, participant observation, and in-depth interviews with 12 key informants. The findings revealed that the “Miracle First 1,000 Days of Life” project represents the state’s efforts to manage and control citizen bodies from early life stages, through the construction of knowledge regimes concerning maternal care during pregnancy, maternal nutritional governance to ensure child well-being, and early childhood nurturing. Medical knowledge and health officials thus function as state agents in the biopolitical regulation of maternal and child bodies. This study challenges the notion of governmentality, showing that biopolitical governance is neither linear nor absolute. Families and health practitioners do not merely follow state health norms; they negotiate, adapt, and reinterpret guidelines according to their contexts. These practices reveal the contingent, negotiated nature of biopolitical power and how individuals actively construct multiple subjectivities within state governance.